2013
DOI: 10.1542/peds.2012-3947
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits in Children With and Without ADHD

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Studies examining the prevalence and associated features of autistic traits (ATs) in children with ADHD with exclusionary autism spectrum disorders suggest that children with ATs exhibit more severe social and interpersonal dysfunction reminiscent of the deficits in children with autism spectrum disorders. WHAT THIS STUDY ADDS:Our results suggest that ATs are overrepresented in ADHD children when compared with control subjects. They also suggest that the presence of ATs is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
76
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 52 publications
(58 reference statements)
11
76
1
4
Order By: Relevance
“…This is important, as children who have ADHD and comorbidities respond optimally to a combination of medication and behavioral interventions. 29 Our finding of a high prevalence of ASD in our ADHD cohort is consistent with recent literature, 30 and is of interest given that DSM-V now permits the concurrent diagnoses of ADHD and ASD. 31 Consistent with previous research, 32 peer problems were elevated in our ADHD group, with large effect sizes observed.…”
Section: Discussionsupporting
confidence: 89%
“…This is important, as children who have ADHD and comorbidities respond optimally to a combination of medication and behavioral interventions. 29 Our finding of a high prevalence of ASD in our ADHD cohort is consistent with recent literature, 30 and is of interest given that DSM-V now permits the concurrent diagnoses of ADHD and ASD. 31 Consistent with previous research, 32 peer problems were elevated in our ADHD group, with large effect sizes observed.…”
Section: Discussionsupporting
confidence: 89%
“…En cuanto al ámbito de la severidad de la sintomatología, los resultados obtenidos en nuestra investigación indican que la presencia del TDAH en los sujetos diagnosticados con TEA aumenta significativamente la severidad de la propia sintomatología autista (Gadow et al, 2006;Rao y Landa, 2014;Sprenger et al, 2013;Yerys et al, 2009), la presencia de rabietas y problemas de conducta (Goldin et al, 2013;Grzadzinski et al, 2011;Jang et al, 2013b;Konst et al, 2013;Yerys et al, 2009), e igualmente aumenta la severidad de la sintomatología depresiva y otros trastornos internalizantes (Grzadzinski et al, 2011;Kotte et al, 2013).…”
Section: Discussionunclassified
“…Por otra parte, diversos estudios se han propuesto estudiar si la comorbilidad de TEA y TDAH tiene un efecto en la severidad de las conductas autistas (Gadow, DeVincent y Pomeroy, 2006;Goldstein y Schwebach, 2004;Rao y Landa, 2014;Sprenger et al, 2013;Yerys et al, 2009), en la severidad de los comportamientos disruptivos (Holtmann, Bölte y Pustka, 2007; Goldin, Matson, Tureck, Cervantes y Jang, 2013;Grzadzinski et al, 2011;Jang, Matson, Cervantes y Goldin, 2013b;Konst, Matson y Turygin, 2013;Tureck, Matson, May y Turygin, 2013;Yerys et al, 2009), o en la sintomatología depresiva y otros trastornos internalizantes (Grzadzinski et al, 2011;Holtmann et al, 2007;Kotte et al, 2013). El enfoque que han adoptado la mayoría de estos trabajos es el de la comparación de la severidad de la sintomatología en al menos 2 grupos: un grupo de sujetos con TEA+TDAH y uno o dos grupos de sujetos que presentaban solo uno de estos diagnósticos de manera aislada.…”
Section: Severidad De Las Conductas Autistas Y De Los Comportamientosunclassified
“…Kotte et al (2013) found that children with AD/HD and autistic traits were more likely to have more problems with siblings than children with AD/HD alone. Kotte et al (2013) also found that AD/HD children with autistic traits had a higher rate of pregnancy and infancy complications than other children with AD/HD alone. The authors commented that prenatal and perinatal complications alone, or in combination with genetic risk factors could account for the development of autistic traits in some children with AD/HD.…”
Section: Parental Stress and Psychological Distressmentioning
confidence: 94%